KOMPETENSI STRATEGIS MATEMATIS PESERTA DIDIK KELAS XI SMK PADA MATERI SISTEM PERSAMAAN LINIER TIGA VARIABEL - Ikhsan Baihaqi; Kiki Nia Sania Effendi (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
The purpose of this study is to describe the mathematical strategic competence of students at the Vocational High School (VHS) level on the material of the Three Variable Linear Equation System (TVLES). The type of research used is descriptive qualitative research. The research subjects were 12 students from class XI AK in one of the vocational schools in Karawang Regency. Methods of data  collection  using  a  test  instrument.  The  data  was  processed  with  descriptive statistics to determine the high, medium, low criteria of the 12 students. Based on the results of the analysis, the average value of the subject's data is 66.67, which is still below the Minimum Completeness Criteria (KKM) for mathematics at the school. From the results obtained, the researcher describes that students with high strategic competence abilities  are  able  to  fulfill  the  three  indicators,  namely  formulating,  representing,  and  solving problems, students with moderate strategic competencies tend to be better at representing indicators, and subjects with moderate abilities. low has low achievement on each indicator